Genetisk variation av betydelse för mjölkkvalitet i Rödkullerasen - Umeland, Petra (2006)
The Swedish Red Polled breed is threatened by extinction and there are only around 1100 animals left. The breed was popular in the early twentieth century, but since then the numbers have steadily decreased. The overall objective of this study was to find out whether there may be economic incentives for preserving the breed. The milk quality properties are of major importance in the production of dairy products. Therefore we would like to establish if the Swedish Red Polled breed carries favourable alleles at loci of relevance for milk quality, to potentially make the breed more interesting for milk production.